Analysis of the quantitative differences in the thickness of the retinal nerve fibre layer between time-domain and spectral-domain optical coherence tomography in patients with relapsing-remitting multiple sclerosis - Gonzalez-Gomez, A; Garcia-Ben, A; Soler-Garcia, A; Garcia-Basterra, I; Padilla-Parrado, F; Garcia-Campos, J M (Revista de neurologiá, 2018)
Optical coherence tomography (OCT) is a tool that is increasingly more commonly used in the study of neuro-degenerative diseases. To analyse and correlate the thickness of the retinal nerve fibre layer (RNFL) by means of time-domain and spectral-domain OCT in patients with relapsing-remitting multiple sclerosis (MS), with and without a history of optic neuritis (ON). We conducted a cross-sectional study of the thickness (mean and by quadrants) of the RNFL of 15 disease-free subjects, 28 with MS with no prior history of ON and 18 with a history of ON. The full ophthalmologic examination included measurement of the RNFL by means of time-domain and spectral-domain tomography. Statistically significant differences are found between the two tomography scans on comparing the mean thickness of the RNFL of the control group (p = 0.000), the group with a history of ON (p = 0.000) and the group without ON (p = 0.000). We obtained a strong, statistically significant and directly proportional correlation between the mean thickness of the RNFL measured with the two types of tomography in the control group (rho = 0.842; p = 0.000), and the groups of eyes without ON (rho = 0.91; p = 0.000) and with ON (rho = 0.902; p = 0.000). There is a strong correlation between the two tomography scans in the measurement of the thickness of the RNFL in patients with MS, with and without a history of ON. Time-domain OCT quantifies greater thicknesses, and therefore both types of tomography have proven to be effective in the study of MS, although the results cannot be interchanged or extrapolated.